2015
DOI: 10.3797/scipharm.1411-14
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-Platelet Activity of Thiosulfonate Derivatives Containing Quinone Moiety

Abstract: Thiosulfonate derivatives based on quinones were synthesized for studying “structure-activity relationship” compounds with an acylated and a free amino-group. Anti-platelet activity of the synthesized compounds was determined and the influence of substituents on the activity of the derivatives was assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…(ii) The inhibition of platelet aggregation by 2-alkoxy-1,4-naphthoquinone increases with 2-alkoxy chain length (Lien et al, 2002 ). (iii) The inclusion of a free amino group in the thiosulfonate moiety of quinone (4-aminobenzenesulfonothioic acid S-[(9,10-dihydro-1,4-dimethoxy-9,10-dioxo2-anthracenyl)methyl] ester) increased its antiplatelet activity (Bolibrukh et al, 2015 ), (iv) The inhibition of platelet activation by alpha-tocopherol quinone is greater than that of vitamin E (Rao et al, 1981 ), and (v) gem -diethyl/methyl substitutions and the addition/modifications of the third ring of ortho -carbonyl hydroquinone scaffold influence on the selective index (IC 50 TRAP-6/IC 50 Collagen) and the inhibitory capacity of platelet aggregation (Mendez et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) The inhibition of platelet aggregation by 2-alkoxy-1,4-naphthoquinone increases with 2-alkoxy chain length (Lien et al, 2002 ). (iii) The inclusion of a free amino group in the thiosulfonate moiety of quinone (4-aminobenzenesulfonothioic acid S-[(9,10-dihydro-1,4-dimethoxy-9,10-dioxo2-anthracenyl)methyl] ester) increased its antiplatelet activity (Bolibrukh et al, 2015 ), (iv) The inhibition of platelet activation by alpha-tocopherol quinone is greater than that of vitamin E (Rao et al, 1981 ), and (v) gem -diethyl/methyl substitutions and the addition/modifications of the third ring of ortho -carbonyl hydroquinone scaffold influence on the selective index (IC 50 TRAP-6/IC 50 Collagen) and the inhibitory capacity of platelet aggregation (Mendez et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been observed that some quinone and hydroquinone compounds protect mitochondrial damage and platelet activation generated by ROS (Kim et al, 2001 ; Cocheme et al, 2007 ); in this way, some structure-activity relationship studies with quinone derivatives have been reported (Chang et al, 1997 ; Cho et al, 1997 ; Kim et al, 2001 ). However, given the variability of the mechanisms of action of quinones-hydroquinones it has been suggested that there is a low selectivity on their antiplatelet activity (Bolibrukh et al, 2015 ; Chang et al, 2019 ; Mendez et al, 2020 ). Recent work has shown conflicting results (Fuentes et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…were developed, which are capable of inhibiting ADP receptors, thereby reducing the risk of thrombosis [16,17]. It is known that some sulfur-containing organic compounds are effective inhibitors of platelet aggregation [9,11,18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Various sulfur-containing organic compounds have a particular importance in such researches. Among these compounds, S-esters of thiosulfonic acids are reported to be valued sulfonating agents and have a wide range as well as a high level of biological activities [9][10][11]. Thiosulfoesters are the close structural analogues of phytoncides of garlic (Allium sativum L.), onion (Allium cepa L.) [10].…”
mentioning
confidence: 99%
“…Quinoid compounds and nitrogen-containing heterocycles are widespread and important building blocks of natural molecules and important structures in synthetic chemistry. Heterocyclic quinone derivatives have been described in the literature as compounds exhibiting antithrombotic [1,2], antimicrobial [3] and anticancer activity [4,5]. Such wide applications determine the relevance of the choice of research objects aimed at developing synthetic approaches to polyfunctional compounds based on quinones and nitrogen heterocycles.…”
Section: Introductionmentioning
confidence: 99%